How does liver steatosis affect diagnostic performance of 2D-SWE.SSI: assessment from aspects of steatosis degree and pathological types. - Huang, Zeping; Zhou, Jing; Lu, Xue; Zhang, Ting; Xu, Shicheng; Jin, Jieyang; Zheng, Rongqin; Chen, Shigao (European Radiology, 2021)
Objective: Two-dimensional shear wave elastography performed by SurperSonics (2D-SWE.SSI) performs well in evaluating liver fibrosis. Steatosis is one of confounding factors which might decrease accuracy, and its effect on 2D-SWE.SSI is still controversial. Our purpose is to evaluate the diagnostic performance of 2D-SWE.SSI affected by different steatosis stages and pathological types in chronic hepatitis B (CHB) patients.Methods: 2D-SWE.SSI was performed on 1306 CHB patients. All patients were divided into mild steatosis, moderate to severe steatosis, and non-steatosis groups. Subgroup analysis was performed according to pathological type. Liver biopsy was reference standard. Propensity score matching was performed to adjust for differences in patient characteristics. The median values of different steatosis group were compared by non-parametric tests before and after propensity score matching. The area under the receiver operating characteristic curve (AUC) was analyzed to assess the diagnostic performance in different steatosis groups.Results: The median values were not significantly different in different steatosis degrees expected in F0-1 patients. The AUC of 2D-SWE.SSI was not affected by different stages of liver steatosis for cirrhosis (= F4) (0.896, 0.853, 0.929, p = 0.34). The high AUCs (0.847, 0.856) were achieved in the non-steatosis and mild steatosis groups, and all were significantly higher than those of the moderate to severe steatosis group for ≥ F2. Moreover, the panacinar type had the best AUC (0.980 for F4 and 0.930 for ≥ F2).Conclusion: In conclusion, moderate to severe steatosis affects 2D-SWE.SSI in CHB patients. These patients had high LSM values in patients with F0-1 and lower accuracy in ≥ F2. Patients with panacinar steatosis have the highest overall diagnostic performance.Key Points: • 2D-SWE.SSI was widely used in evaluating liver fibrosis and it has many confounding factors. Steatosis is one of the confounding factors and its effect on 2D-SWE.SSI was controversial. • Our study based on 1306 CHB patients with liver biopsy found that 2D-SWE.SSI might be affected by moderate to severe liver steatosis in diagnostically significant fibrosis (≥ F2) of CHB patients. • Patients with steatosis of the panacinar type have the highest overall diagnostic performance.